Estudo do Capim Vetiver (Chrysopogon zizanioides (l.) Roberty) na área ambiental: revisando aplicações - Souto, Aline Rafaela Rodrigues (2022)
Due population growth and society development, the number of activities carried out that generate negative impacts on the environment has increased. Incorrect disposal of solid waste and liquid waste is responsible for contaminating water and soil, triggering a number of environmental, economic and social problems. Such residues depending on their origin, such as industrial wastewater and electronic waste, may contain heavy metals, wich are harmful to environmental balance. Domestic wastewater, on the other hand, has a high load of organic matter, which, in excess, generates decrease of the oxygen available for aquatic species. With the growth and development of society, in addition to natural resources being negatively impacted, they are used intensely, such as soil exploration, and consequently there are losses of nutrients and important characteristics of it. Currently, in the field of research, techniques have been studied and analyzed in order to remedy negative impacts on the environment. Biotechnology comes as a way to provide cost-effective positive techniques, since they are environmentally appropriate and low cost when compared to other traditional techniques. In the field of biotechnology there is phytoremediation, a technique that uses plants in order to perform environmental recovery, reducing or eliminating the toxicity of contaminants from the environment. One plant used is Vetiver grass (Chrysopogon zizanioides (L.) Roberty), which known for its physiological, morphological and ecological characteristics important for such application. The present research had as main objective to analyze different applications of species in environmental area. Results obtained in the study were a broad area of research of Vetiver grass use in phytoremediation process, both for water and soil contaminated treatment by heavy metals, as well as for removal of nitrogen and phosphorus from domestic sewage and in soil and slopes protection. It was possible to verify the efficiency of the species in removal of contaminants when compared with other species, as well as role of Vetiver in protection of soil and slopes in addition to other promising applications of species in environmental area, being efficiency of use of plant related to characteristics of the same. It was concluded that the specie studied in phytoremediation process showed significant efficiency in removal of heavy metals in water bodies and soil. Furthermore, it proved to be efficient in removal of nitrogen (N) from domestic sewage and also phosphorus (P). Soil and slopes protection by species proved to be efficient with increasing soil shear resistance. Other applications proved positive for use of plant, giving openness to future studies of technique using Vetiver grass.